Heterodinuclear Ruthenium(II) Complexes of the Bridging Ligand 1, 6, 7, 12‐Tetraazaperylene with Iron(II), Cobalt(II), Nickel(II), as well as Palladium(II) and Platinum(II). Issue 1 (26th November 2015) - Brietzke, Thomas; Kelling, Alexandra; Schilde, Uwe; Mickler, Wulfhard; Holdt, Hans‐Jürgen
Abstract: The first heterodinuclear ruthenium(II) complexes of the 1, 6, 7, 12‐tetraazaperylene (tape) bridging ligand with iron(II), cobalt(II), and nickel(II) were synthesized and characterized. The metal coordination sphere in this complexes is filled by the tetradentate N, N ′‐dimethyl‐2, 11‐diaza[3.3](2, 6)‐pyridinophane (L‐N4 Me2 ) ligand, yielding complexes of the general formula [(L‐N4 Me2 )Ru(µ‐tape) M (L‐N4 Me2 )](ClO4 )2 (PF6 )2 with M = Fe [2 ](ClO4 )2 (PF6 )2 , Co [3 ](ClO4 )2 (PF6 )2 , and Ni [4 ](ClO4 )2 (PF6 )2 . Furthermore, the heterodinuclear tape ruthenium(II) complexes with palladium(II)‐ and platinum(II)‐dichloride [(bpy)2 Ru(μ‐tape)PdCl2 ](PF6 )2 [5 ](PF6 )2 and [(dmbpy)2 Ru(μ‐tape)PtCl2 ](PF6 )2 [6 ](PF6 )2 , respectively were also prepared. The molecular structures of the complex cations [2 ] 4+ and [4 ] 4+ were discussed on the basis of the X‐ray structures of [2 ](ClO4 )4 · MeCN and [4 ](ClO4 )4 · MeCN. The electrochemical behavior and the UV/Vis absorption spectra of the heterodinuclear tape ruthenium(II) complexes were explored and compared with the data of the analogous mono‐ and homodinuclear ruthenium(II) complexes of the tape bridging ligand. Abstract :